Families of scroll grid attractors - Yalçin, Müstak E.; Suykens, Johan A. K.; Vandewalle, Joos; Özoguz, Serdar (World Scientific Pub Co Pte Lt, 2002)
In this paper a new family of scroll grid attractors is presented. These families are classified into three called 1D-, 2D- and 3D-grid scroll attractors depending on the location of the equilibrium points in state space. The scrolls generated from 1D-, 2D- and 3D-grid scroll attractors are located around the equilibrium points on a line, on a plane or in 3D, respectively. Due to the generalization of the nonlinear characteristics, it is possible to increase the number of scrolls in all state variable directions. A number of strange attractors from the scroll grid attractor families are presented. They have been experimentally verified using current feedback opamps. Also Lur'e representations are given for the scroll grid attractor families.
Keywords: scroll attractors; Complex behavior and chaotic systems of ordinary differential equations; strange attractors; equilibrium points; Applications of dynamical systems; Lur'e representations; Strange attractors, chaotic dynamics of systems with hyperbolic behavior